(3GdCfHGA GdeMceI aj GdCSeGA GdeHgeIs - (3GdNWjH GdHZOGOj , CMeO Hf Ydj Hf KGHJ , CHh HcQ , J (B463 (3g` s ((3eMeO Hf CHj HcQ Hf eMeO GdOeTbi GdTGaYi s)
(3ChdgG (B:s
(3CNHQfG GdTjN aLQ GdOjf CHh GdMSf Ydi GdebOSi MOKfG bGd (B: (3GdMeO ddg EdgfG hehdGfG caGA EfYeGeg hCaVGdg s
(3BNQgG (B:s
(3ef JQLeI (B" (3NfSGA HfJ NPGe GdCfUGQjI (B" (3afcMJ HYO Pdc CfG GHGHI GdGfUGQI hcGfJ KjHkG , bGd (B: (3CNHQJ CfgG NfSGA HfJ NPGe ef Cgd bHGGHf LQjL BNQ GdLRA GdChd s
(3GdfSNI ebGHdI hcJH GdebGHdI CMeO Hf eMeO GdYSLOi Ke ebGHdI CNQi ddHQGRGdi eY YeQ Hf GdaGQbis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B172s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs